NON-FERMENTING GRAM-NEGATIVE BACILLI ISOLATES FROM VARIOUS CLINICAL SAMPLES AND THEIR ANTIBIOTIC SUSCEPTIBILITY PATTERN AT A TERTIARY CARE HOSPITAL - C., PRAVEETHA; PRAKASH, G. N. RAVI; LAVANYA, VALLURI ANITHA; SRIVANI, NELLORE (International Journal of Current Pharmaceutical Research, 2024)
Objective: Non-fermenting Gram-negative bacilli (NFGNB) were once considered as a common laboratory contaminant (15-20%), but in recent years they have emerged as a major concern for nosocomial infections as the frequency of their isolation and resistance towards antimicrobial agents is increasing rapidly. Infections caused by these bacteria are almost always secondary to some predisposing factors in patients such as burns, prolonged antimicrobial therapy, immunosuppression etc. The major problem leading to high mortality lies in the appearance of drug-resistant strains. The Objectives of the study was to identify and isolate NFGNB and study their antibiogram profile so that empirical therapy could be selected accordingly. Methods: This is a cross-sectional study conducted in the Department of Microbiology, Sri Venkateswara Medical College, Tirupati for a period of 6 mo. A total of 7875 various clinical samples were received and processed. Isolates were tested against 8 different antibiotics by a Kirby-Bauer disk diffusion method. Results: Out of 7875 clinical samples processed, 2666 samples showed culture positive, among which 539 samples (20%) were NFGNB isolates. Male to female ratio was 1.5:1. Most common age group affected was 41-60 y. Predominant NFGNB isolates were Pseudomonas species (73.47%) followed by Acinetobacter species (26.53%). Pus (42%) was the commonest sample from which NFGNB was isolated; followed by Urine (16.88%), Sputum (16.69%), Blood (15.39%), ET tube (6.30%), Body fluids (1.66%) and cervical/vaginal swabs (1.11%). Both isolates showed higher resistance towards cephalosporins followed by ciprofloxacin, whereas least resistance towards Meropenem followed by Imipenem. Most of the isolates showed multidrug resistance (MDR). Conclusion: Antimicrobial resistance (AMR) should be monitored on a regular basis in hospital settings. This study suggests that due care must be taken to adequately diagnose NFGNB infections and prescribe the antibiotic treatment most effective in preventing the increase in multidrug-resistant strains.